1982
DOI: 10.1111/j.1365-2621.1982.tb12743.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage Characteristics of Brown Shrimp (Penaeus aztecus) Stored in Retail Packages Containing CO2‐Enriched Atmospheres

Abstract: The use of modified atmospheres containing C02 was effective in retarding microbial growth during refrigerated storage of retail packaged fresh brown shrimp (Penaeus aztecus). The inhibitory effcct seemed proportional to the C02 tension. The surface pH of shrimp stored in air increased rapidly during the initial storage period while a decrease in pH occurred in all the samples stored in C02enriched atmospheres. Shrimp stored in modified atmospheres also had significantly lower total volatile nitrogen (TVN) val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 15 publications
4
24
2
2
Order By: Relevance
“…This is in contrast to increases in CO 2 levels after storage reported by Layrisse and Matches (1984). Under identical conditions to the current study, Lannelongue et al (1982) also found only a slight increase in CO 2 after storage of packed shrimp.…”
Section: Headspace Analysiscontrasting
confidence: 56%
See 2 more Smart Citations
“…This is in contrast to increases in CO 2 levels after storage reported by Layrisse and Matches (1984). Under identical conditions to the current study, Lannelongue et al (1982) also found only a slight increase in CO 2 after storage of packed shrimp.…”
Section: Headspace Analysiscontrasting
confidence: 56%
“…The microbial loads under MAP in the current study were also much lower at the end of shelf life than those identified by Mastromatteo et al (2010), even though their peeled prawns had much lower initial counts. Lannelongue et al (1982) found a similar gas mixture to the current trials prolonged the lag phase as compared to those stored in air. Layrisse and Matches (1984) obtained initial slower growth of bacteria during air storage of Pandalus platyceros after using similar postharvest MAP storage conditions.…”
Section: Microbiological Testingmentioning
confidence: 86%
See 1 more Smart Citation
“…Lannelongue, Finne, Hanna, Nickelson and Vanderzandt (1982) reported a drop in surface pH in MAP products due to the dissociation of CO to 2 carbonic acid (proportional to CO concentration).…”
Section: Discussionmentioning
confidence: 97%
“…Most of these articles refer to cooked shrimps, whether chilled or frozen [14,15,16], and very few refer to fresh shrimps [17,18]. Moreover, they discuss microorganism-induced spoilage rather than melanosis.…”
Section: Introductionmentioning
confidence: 99%